Associations between Consumption of Ultra-Processed Foods and Intake of Nutrients Related to Chronic Non-Communicable Diseases in Mexico (2019)
ABSTRACT: Background Ultra-processed foods are highly palatable and can be consumed anywhere at any time, but typically have a poor nutritional profile. Therefore, their contribution to total energy intake has been proposed as an indicator for studying overall dietary quality. Objective The aim of this study was to investigate the associations between the energy contribution from ultra-processed foods and the intake of nutrients related to chronic non-communicable diseases in Mexico. Design This study used a secondary analysis of cross-sectional data from the 2012 Mexican National Health and Nutrition Survey. Participants/setting This study included participants aged 1 year and older (n¼10,087) who had completed a 1-day 24-hour recall. Main outcome measures Intake from added sugar (% kcal), total fat (% kcal), saturated fat (% kcal), protein (% kcal), dietary fiber (g/1,000 kcal), and dietary energy density (kcal/g) were measured. Statistical analysis Multiple linear regression models adjusted for sociodemographic variables were fitted to assess the association between quintiles of energy contribution from ultra-processed foods and nutrient intake. Results Mean reported energy contribution from ultra-processed foods to the Mexican population’s diet ranged from 4.5% kcal in quintile 1 (Q1) to 64.2% kcal in quintile 5 (Q5). An increased energy contribution from ultra-processed foods was positively associated with intake from added sugar (Q1: 7.4% kcal; Q5: 17.5% kcal), total fat (Q1: 30.6% kcal; Q5: 33.5% kcal) and saturated fat (Q1: 9.3% kcal; Q5: 13.2% kcal), as well as dietary energy density (Q1: 1.4 kcal/g; Q5: 2.0 kcal/g) (P0.001); and inversely associated with intake from protein (Q1: 15.1% kcal; Q5: 11.9% kcal) and dietary fiber (Q1: 16.0 g/1,000 kcal; Q5: 8.4 g/1,000 kcal) (P0.001). Conclusions In the Mexican population, an increased energy contribution from ultraprocessed foods was associated with a lower dietary quality with regard to intake of nutrients related to chronic non-communicable diseases. Future research is needed to identify barriers to eating a variety of unprocessed and minimally processed foods for the Mexican population, as well as effective public health strategies and policies to overcome these barriers.